(untitled) (Fiep Bulletin - online, 2013)
The present study it broke of an experience pilot in the direction to develop a proposal intervening with an educative software as resource directed to the alfabetização of children in the initial series of basic education with difficulties of learning in the process of alfabetização in a particular school of small transport in the city of Is Gonçalo, Been of Rio De Janeiro. The metodológicas strategies had been guided by the accomplishment of comment of the dynamics of the interview and classroom carried through next to the teacher and parents of the pupils, associates to the procedures of the “ecological insertion”. This methodology makes possible to the necessary researcher the contextual immersion for analyzes of the relations/interactions between the pupils and its environment of development. In accordance with the ecology of the human development so that this analysis is possible we will use the Bioecológica Theory of Desenvolvimento Humano (TBDH) of similar Bronfenbrenner to study (process, person, context and time). The results had demonstrated that the resources applied in the pertaining to school environment, in relation to these pupils iram to favor its inclusion in the decurrent pertaining to school process of the alfabetização. However, one becomes necessary study, research to extend the knowledge, to develop and to test forms that make possible the true inclusion in the pertaining to school flow.